Uniparental Disomy of Chromosome 2 Unmasks New ITGA6 Recessive Mutation and Results in a Lethal Junctional Epidermolysis Bullosa in a Newborn - Rebecca Higgins; Annika N. Jensen; Julian Wachstein; Leena Bruckner-Tuderman; Roland Spiegel; Hubert Traber; Josef Achermann; Martin Schaller; Birgit Fehrenbacher; Martin Röcken; Desislava Ignatova; Yun-Tsan Chang; et al. (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)